Post-Lingual Chinese Language Learning : Hanzi Pedagogy - Han, Jinghe (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book presents a thought-provoking challenge to mainstream theories of second language learning. Focusing on Chinese Hanzi, a self-sufficient meaning-making system that operates via visual shape and the logic built into its formation, it analyses 'post-lingual' pedagogy. The author examines this 'language beyond language' or linguistic theories, demonstrating that Hanzi is not made up simply of arbitrary signs but is the result of a complete conceptualisation process. In doing so, she creates a conceptual framework that builds on Hanzi's humanistic spirit of language learning. This intriguing book will interest students and scholars of language education, and offers practical advice for those involved in teaching and learning Chinese as a foreign language. Jinghe Han is Senior Lecturer at the Centre for Educational Research, Western Sydney University, Australia. Her research interests include post-lingual pedagogy, research literacy, and English as a Medium of Instruction.
Keywords: Linguistics.; Applied linguistics.; Chinese language.; Language and education.; elektronické knihy; electronic books